The Relationship Between Teachers Perception and Belief on Readiness to Plan a Learning of Early Childhood Education Program Teachers - Yoesoep Edhie Rachmad; Devin Mahendika; Nana Citrawati Lestari; Fitria Meisarah; Reza Saeful Rachman (Edumaspul: Jurnal Pendidikan, 2023)
This study sought to ascertain whether there was a correlation between belief in readiness to plan teaching and learning activities, believe in perceptions of PAUD teachers, and readiness to plan teaching and learning activities. Quantitative research with a correlational design was used in this study. A questionnaire was employed as the study's instrument, and a simple random sampling technique was used to select the sample. In terms of hypothesis testing, the researcher used product moment correlation with the results that there was a positive relationship between beliefs and perceptions of PAUD teachers, there was no relationship between beliefs about the readiness to plan STEAM-based learning, and there was no relationship between perceptions of readiness to plan. STEAM-based learning.